ALTERNATING DIRECTION IMPLICIT METHOD FOR SOLVING MODIFIED REYNOLDS EQUATION IN A LUBRICATED SLIDING CONTACT - M. Tauviqirrahman; R. Ismail; . Jamari; Schipper D. J. (Prosiding SNST Fakultas Teknik, 2010)
Reynolds lubrication theory assumes that there is no-slip boundary on the interfaces between solid and lubricant. However, during the past few years, slip boundary has been observed in micro/nanometer gap. In this paper, numerical studies of the Reynolds model with slip boundary are presented for investigating the effect of slip boundary on the pressure distribution  in sliding contact. The modified Reynolds equation is solved numerically by finite difference method with alternating direction implicit algorithm. Line by line algorithm was applied to overcome multidimensional direction. The simulation results indicate that the two-dimensional modified Reynolds equation can predict the dynamic of lubrication process with boundary slip in sliding contact. Keywords : Slip boundary, finite difference method, hydrophobic, hydrophilic